Insentif Pajak Dalam Membentuk Keputusan Investasi - Wika Arsanti Putri (Universitas Bina Sarana Informatika, 2017)
This literature review discusses the effectiveness of tax incentives in attracting investment. The author analyzes the theory of investment that says that tax incentives reduce the use of capital stock can increase investment. However, there are still doubts over tax incentive policies that can increase investment. This is due to other factors considered by investors in investing such as the ease of licensing, the size of the domestic market, international market access, infrastructure, social conditions and security, and the availability of human resources.